2017
DOI: 10.1016/j.jjcc.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative ascorbic acid supplementation does not reduce the incidence of postoperative atrial fibrillation in on-pump coronary artery bypass graft patients

Abstract: The results of this study do not support the effectiveness of ascorbic acid supplementation in reducing the incidence of postoperative atrial fibrillation in elective on-pump CABG patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The remaining 53 articles were assessed for eligibility. Notable exclusions were due to pre- or perioperative administration for scheduled cardiac (n = 14), 40 53 gastrointestinal (n = 1), 54 vascular (n = 1), 55 or gynecologic (n = 1) 56 surgery, administration as part of combination therapy with other agents (n = 27), 27 31 , 57 – 78 or case reports (n = 3). 79 81 Many of the above were also excluded due to enteral administration.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 53 articles were assessed for eligibility. Notable exclusions were due to pre- or perioperative administration for scheduled cardiac (n = 14), 40 53 gastrointestinal (n = 1), 54 vascular (n = 1), 55 or gynecologic (n = 1) 56 surgery, administration as part of combination therapy with other agents (n = 27), 27 31 , 57 – 78 or case reports (n = 3). 79 81 Many of the above were also excluded due to enteral administration.…”
Section: Resultsmentioning
confidence: 99%
“…The full text of the remaining 26 trials was reviewed for detailed evaluation, and 17 RCTs were included in qualitative synthesis. Finally, 13 trials were involved for quantitative analysis . The flow chart of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Though the definition of POAF varied among the trials, the main characteristic is an episode of AF lasting beyond a certain period or requiring urgent intervention. Among the thirteen included studies, all reported the POAF events; eleven of them reported it as the primary outcome; nine of them reported HLOS; eight reported ICU length of stay; and eight reported the adverse events . The risk of bias of the included studies was high in three studies, unclear in five studies, and low in five studies (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Existing evidence indicating whether perioperative use of vitamin C can reduce the incidence of postoperative AF is still inconsistent. [19][20][21] This difference in results may be due to different regimens of vitamin C.…”
Section: Discussionmentioning
confidence: 99%